2014
DOI: 10.1016/j.jcf.2013.10.007
|View full text |Cite
|
Sign up to set email alerts
|

BIIL 284 reduces neutrophil numbers but increases P. aeruginosa bacteremia and inflammation in mouse lungs

Abstract: Background A clinical study to investigate the leukotriene B4 (LTB4)-receptor antagonist BIIL 284 in cystic fibrosis (CF) patients was prematurely terminated due to a significantly increased risk of adverse pulmonary events. We aimed to establish the effect of BIIL284 in models of Pseudomonas aeruginosa lung infection, thereby contributing to a better understanding of what could have led to adverse pulmonary events in CF patients. Methods P. aeruginosa DNA in the blood of CF patients during and after acute p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 23 publications
1
50
0
Order By: Relevance
“…Importantly, however, note that AAT did not cause complete inhibition of LTB 4 -BLT1 engagement, and this is a further important attribute of AAT as an LTB 4 antagonist. To date, BLT1 antagonists in vivo have been limited by safety issues related to almost complete inhibition of LTB 4 (90). In light of the results of this study, AAT augmentation therapy may serve as an additional treatment strategy in management of patients with LTB 4 -driven diseases.…”
Section: Discussionmentioning
confidence: 91%
“…Importantly, however, note that AAT did not cause complete inhibition of LTB 4 -BLT1 engagement, and this is a further important attribute of AAT as an LTB 4 antagonist. To date, BLT1 antagonists in vivo have been limited by safety issues related to almost complete inhibition of LTB 4 (90). In light of the results of this study, AAT augmentation therapy may serve as an additional treatment strategy in management of patients with LTB 4 -driven diseases.…”
Section: Discussionmentioning
confidence: 91%
“…While this result suggests that limiting pathology by inhibiting PMN influx might be beneficial, the increased bacterial burdens and likelihood of dissemination to extraocular tissues (25) in the face of PMN deficiencies likely preclude such an approach. An analogous situation was found in humans, wherein inhibition of neutrophil influx into the lungs of cystic fibrosis (CF) patients infected with P. aeruginosa by an experimental anti-inflammatory drug, BIIL 284 (26), resulted in early termination of the clinical trial due to worse outcomes in treated patients (27).…”
Section: Therapeutic Efficacy Of Monoclonal Antibody To Pnag In Staphmentioning
confidence: 82%
“…Interestingly, the study reported higher airway inflammation despite reduced neutrophils and an increase in discontinuation due to infections [108]. One concern regarding anti-inflammatory drugs has been the potential that reducing neutrophil numbers could lead to uncontrolled bacterial infection, as occurred in a previous trial of a leukotriene B4 receptor antagonist in cystic fibrosis [109,110]. Statins have immunomodulatory effects and may have a role in neutrophilic inflammation.…”
Section: Figurementioning
confidence: 99%